2016
DOI: 10.1007/s00395-016-0599-5
|View full text |Cite
|
Sign up to set email alerts
|

MD2 mediates angiotensin II-induced cardiac inflammation and remodeling via directly binding to Ang II and activating TLR4/NF-κB signaling pathway

Abstract: Angiotensin II (Ang II) induces cardiac inflammation and remodeling. Emerging evidence indicates that Ang II may utilize the Toll-like receptor 4 (TLR4) signaling pathway in mediating pro-inflammatory and pro-fibrotic activities. However, the precise mechanism is poorly understood. Myeloid differentiation 2 (MD2), a molecule that physically binds to TLR4, confers lipopolysaccharide responsiveness and may also be involved in mediating the actions of Ang II. We hypothesize that MD2 plays an essential role in car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
52
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 41 publications
5
52
0
Order By: Relevance
“…Surface plasmon resonance (SPR) spectroscopy further evaluated Ang II binding with MD2 and TLR4. In consistent with previous result18, Ang II bound rhMD2 with a high affinity (Supplementary Figure S5C), but failed to bind recombinant human TLR4 protein under the same experimental condition (Supplementary Figure S5D). These data further validate that MD2, rather than TLR4, is the direct target of Ang II in the kidney.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Surface plasmon resonance (SPR) spectroscopy further evaluated Ang II binding with MD2 and TLR4. In consistent with previous result18, Ang II bound rhMD2 with a high affinity (Supplementary Figure S5C), but failed to bind recombinant human TLR4 protein under the same experimental condition (Supplementary Figure S5D). These data further validate that MD2, rather than TLR4, is the direct target of Ang II in the kidney.…”
Section: Resultssupporting
confidence: 92%
“…The present data and previously reported evidence18 from cell-free assays supported direct binding of Ang II with MD2. This direct interaction of Ang II with MD2 was analogous to LPS binding with MD2, resulting in MD2/TLR4 complex formation, and recruitment of adaptor molecules for signaling.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…It is well known that Ang II contributes to hypertension and atherosclerosis. Recently, there have been more studies investigating the molecular mechanisms and effects of Ang II on the blood vessels, including induction of Egr-1 expression [42], AT1R and p38MAPK pathway interactions [43], sphingosine-1-phosphate induced signaling axis [44], and Toll-like receptor 4 (TLR4) signaling pathway [45]. Although it has been demonstrated that Ang II can induce MMP-9 expression in VSMCs via a NF-κB dependent pathway [46], we found the NF-κB binding activity is through AT1R, but not AT2R.…”
Section: Discussionmentioning
confidence: 99%
“…Most TLRs transmit their signals through its down-stream effector myeloid differentiation primary response gene 88 (MYD88), resulting in the activation of nuclear factor-κB (NF-κB) transcription factor and subsequent expression of pro-inflammatory cytokines [19,20]. Mohan et al reported that apigenin can repress autophagy and enhance apoptosis in neuroblastoma cells through TLR-4 and NF-κB suppression [21].…”
Section: Introductionmentioning
confidence: 99%